Mekanisme Penentuan Margin Pada Transaksi Pembiayaan Murabahah - Salsa Bil Dwi Siswi (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2020)
Sharia banks, one of which activities are channeling funds with the principle of Murabahah (Buy-Sell), of course carry out these transactions in accordance with applicable regulations, namely in accordance with the DSN fatwa No. 04 / DSN-MUI / IV2000 regarding Murabahah, which is the contract used in the sale and purchase of goods by stating the cost of goods and the profit (margin) agreed upon by the seller and the buyer. In murabahah in Islamic banks, we as customers have agreed with the bank to buy goods, where the goods are first purchased by the Islamic bank, then sell them back to customers with a predetermined and mutually agreed rate of profit margin. At first glance, we do not see a difference in the amount of installments between installments at conventional banks and those in Islamic banks. What we need to underline here is the form / scheme of each type of channeling funds from the bank. For conventional banks, banks channel funds by providing credit / loans in the form of money. This means that here a conventional bank sells its money in the hope of a profit rate determined by interest. Meanwhile, Islamic banks distribute funds in the form of sale and purchase, where the BS buys an asset / asset which then sells it back to the customer at the level of profit that has been agreed at the beginning. Where according to PBI No. 7/46 / PBI / 2005 that "the agreement margin must be determined once at the beginning of the contract and does not change during the contract period". This shows that there will be no change in installments during the financing period with the Indonesian murabahah scheme